THE EFFECT OF BOARD DIVERSITY ON FINANCIAL PERFORMANCE OF EMPLOYER’S PENSION FUND - Apriani Dorkas Rambu Atahau; Supatmi . (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2011)
Good corporate governance as a concept gains wide public attention especially after the 19971998 financial crises. The falls of many financial institutions is believed related to the absence of good corporate governance. As one of financial institutions which mainly serve for providing future benefits after retirement, Indonesian employer’s pension fund also required to implement good pension fund governance through a regulation from Flead of BAPEPAM-LK Number Kep-136/BL/2006 about the Guidelines of Pension Fund Governance. The implementation of this regulation will give impacts on the board diversity since the board will be the front line in implementing good pension fund governance.The objective of this research is to examine the effect of board diversity to financial performance of Indonesian employer’s pension fund. In this research, board diversity is measured by three variables, i.e. gender, education background and duality. Financial Performance is measured by Return on Investment, Return on Assets and Fund Sufficiency Ratio. Research sample consists of ten employer’s pension fund as members of Indonesian Christian Pension Fund Association who conduct defined benefit program, which possesses complete data from 2006-2009 Association’s Directory. Analysis is done with multiple regressions by controlling pension fund basis, board size and pension fund size. The result finds that board diversity impact employer’s pension fund financial performance. It implies the need to consider board heterogeneity in the election of board member to optimize employer’s fund financial performance.